REGIONAL FEATURES OF INNOVATIVE DEVELOPMENT AND DIFFERENTIATION OF DIRECTIONS OF INNOVATION POLICY OF RUSSIA - DUBOVITSKI, Alexander; Klimentova, Elvira; Rogov, Matvei (Journal of process management and new technologies, 2021)
In our manuscript we have made an attempt to study specific sides of Russian Federation’s innovative development, analyze its impact in economy growth and provide main ways of innovative policy realization in different types of regions. The method is based on partial abstraction from the unique properties of each region, thereby uniting them into homogeneous groups using k-means method. Further analysis of the determination of the main factor at the level of country was carried out using decision trees functions with the subsequent collection of OOB errors. Group analysis was carried out using regression analysis. As a result, the authors obtained five types of regions (with a high, above average, average, below average, low level of innovative development), provided an individual characteristic for each group regarding the innovation development and identified prerogative innovative factors that can be considered by the state as a criterion for differentiating state policy and regulation of the development of innovation policy.
Keywords: economic growth, innovation, innovation climate, public policy